Association of Early Postnatal Transfer and Birth Outside a Tertiary Hospital With Mortality and Severe Brain Injury in Extremely Preterm Infants: Observational Cohort Study With Propensity Score Matching. Issue 2 (June 2020) - Helenius, K.; Longford, N.; Lehtonen, L.; Modi, N.; Gale, C.
Abstract : ( BMJ . 2019;367:1–11) The occurrence of infants born <28 weeks gestation is rare in both the United Kingdom and the United States, but such incidents carry a very high risk of death, neonatal morbidity, and long-term disability. Previous research has indicated that the best outcomes for these infants are achieved when care is given in specialized tertiary hospitals. At-risk pregnant women who present at nontertiary hospitals are often transferred to more specialized facilities either before or after delivery; a number of recent studies have focused on the outcomes of infants who were transferred postnatally, with inconclusive results. These investigators conducted their research to determine if transferred infants had a higher incidence of mortality and severe brain injury compared with nontransferred infants born in tertiary hospitals.